Entrenamiento y adaptación muscular: sustratos y vías metabólicas para la producción de energía - Boffi, Federico Martín (2008)
Three isoforms of MyHc have been characterized in the skeletal muscle of adult equines at the proteins level: types I, IIA and IIX. The distribution of these MyHCs defines three pure kinds of fibre which contain a single isoform (I+IIA and IIAX). The hybrid fibres IIAX exist in the locomotive muscles as a permanent and significant population. The adjusting response may take different forms depending on the nature of the stimulus: hypertrophy, reorganization (restructuring) without hypertrophy and a combined answer, when restructuring joins hypertrophy. The equines may take the most of different energetic subtrates, some of which are used immediately after the ingest, while others are stored in the liver, the muscles or adipose tissue in order to be used later. The muscular glycogen and the glucose may be degraded aerobically through the aerobic pathway or through the anaerobic pathway, while in the endurance exercises the use of fatty acids is accomplished from the degradation of fat stored in the subcutaneous cellular tissue. The oxidative metabolism measures the function of the cardiovascular and respiratory systems. On the contrary, the anaerobic metabolism involves only the muscular tissue.